Optimizing Engine Start Systems with Application to Sailing/Coasting and Mild Hybridization - Madhusudan Raghavan (Advances in Technology Innovation, 2020)
Engine start systems are key to providing a good customer experience for today’s drivers. Considerable effort goes into ensuring a smooth and quiet engine start, especially in vehicles equipped with start/stop systems. We present two novel mechatronic starters that are designed to improve start quality by enabling faster and quieter engine starts. In the first proposed concept, the traditional alternator is replaced with a motor/generator unit that is capable of exerting positive torque on the engine as needed, in addition to the conventional power generation function. The motor/generator is selectively connected to the crankshaft via a selectable geared or belted connection to enable different operating modes. This starter executes a 400 ms faster start for a typical engine when compared to a conventional 12V starter. We also present a second starter that uses an integrated two-speed gear train to crank the engine. The cranking gear ratio is changed from the initial high ratio to a lower ratio once the engine starts to spin. This ratio change allows the starter motor to continue to operate in a favorable torque-speed zone and push the engine to a higher pre-ignition rpm than a conventional starter, resulting in a quieter, smoother start. We also present results from incorporating the belted/geared starter concept in vehicles with sailing/coasting mode as well as in mild hybrid propulsion systems. Sailing/coasting mode of operation is enabled by the quick engine re-start capability of this starter allowing seamless switching between fuelled and unfuelled engine operation. Such an operation could reduce fuel consumption by about 3-6% on the NEDC driving cycle, without regenerative braking. One may further hybridize the propulsion system by adding a battery for storing regenerative braking energy. Using such an architecture, a 6-8% fuel economy improvement on the WLTP certification driving cycle may be achieved, depending on voltage and power levels implemented, as well as energy storage systems included.